Ultrasoft X-ray Spectroscopy Investigation of the Model System Si–SiO2 - Kozhakhmetov, S. K. (Nauka/Interperiodica, 2000)
SiO2 surface films with different thicknesses (ranging from 20 to 630 Å), grown on a crystal silicon substrate, have been investigated by the method of reflection and scattering of ultrashoft X-rays. It is shown on the basis of a simultaneous analysis of the SiL2, 3 reflection spectra and the scattering indicatrix that the critical angle qc for total external reflection for SiO2 at l = 57 Å lies in the range 4.5 °–5°. The angular dependence ofthe thickness of the surface layer that forms the specular reflection is obtained. It is shown that the surface layer,whose thickness corresponds to the penetration depth of the radiation into the material with glancing angle close to the critical value qc, plays a large role in the formation of the anomalous scattering peak (Yoneda peak).